Translation and global spaces of power - Baumgarten, Stefan; Cornellà-Detrell, Jordi (Multilingual Matters, 2018)
This book focuses on the role of translation in a globalising world. It presents a series of case studies that explore the ways in which translation is subject to ideology and power play across diverging domains and genres. Broadly based on a discussion of 'translation and the economies of power', the chapters examine an array of contextual and textual factors, ranging from global, regional and institutional power relations to the linguistic, stylistic and rhetorical implications of translation decisions. The book maps the multiple ways in which power relations and ideological positions affect cross-cultural communication, with special reference to repressive practices in history, translation policies, media power and commercial hegemonies. It concludes that future translation research will benefit from a more sustained emphasis on the power of technology and economic capital.
Keywords: Translating and interpreting -- Social aspects.; Intercultural communication.; Communication interculturelle.; FOREIGN LANGUAGE STUDY -- Multi-Language Phrasebooks.; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General.; LANGUAGE ARTS & DISCIPLINES -- Readers.; LANGUAGE ARTS & DISCIPLINES -- Spelling.; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; Intercultural communication; Translating and interpreting -- Social aspects